Conceptualization of the core (Communication-oriented revitalization enhancement) Perspective as strengthening destination branding in the East Java Mangrove Area - Jupriono, Jupriono; Palupi, Merry Fridha Tri; Andrianto, Novan (Edelweiss Applied Science and Technology, 2024)
The mangrove ecosystems of East Java serve as both critical environmental assets and emerging tourism destinations. However, these destinations face challenges in creating a strong destination brand that connects with tourists and encourages sustainable practices. This paper introduces the CORE (Communication-Oriented Revitalization Enhancement) framework as a conceptual model aimed at strengthening destination branding for the mangrove regions of East Java. CORE integrates communication theories, including Lasswell’s Communication Model, Behaviorism, Public Relations, Mass Communication, and Media Ecology, to build a holistic branding approach. The research utilized participatory action research (PAR) to engage local communities, tourism stakeholders, and visitors in co-developing branding strategies. Results indicate that an integrated communication approach can significantly improve the destination’s image, increase community engagement, and foster sustainable tourism practices. This study provides insights into the application of theoretical frameworks in real-world tourism branding and offers recommendations for implementing effective communication-based strategies for sustainable destination branding.